Suicide Risk Factors among Adolescents: A Narrative Review - Kiani, Zahra; Simbar, Masoumeh; Mokber, Naghmeh; Kiani, Mohammad; Azimi, Nasrin; Kazemi, Samiyeh (Advances in Nursing & Midwifery, 2021)
Introduction: The increasing global rates of adolescent morbidity and mortality highlights problems such as suicide during puberty. Adolescent suicide prevention along with adolescent health in general comprise a priority on the global agenda. Since suicide is associated with several behavioral symptoms, the present study seeks to present a narrative review of suicide risk factors among adolescents. Methods: The present review study was conducted between January 2000 and November 2017 by navigating the Science Direct, Scopus, Web of Science, Cochrane, PsycINFO, Google Scholar and PubMed databases to find relevant articles containing the keywords “suicide” and “adolescent.” Of the 49,450 articles obtained from this search, 85 relevant articles were selected for review. Results: According to the findings of the present study, suicide risk factors can be classified into three categories: Social and community risk factors, relationship risk factors and individual risk factors. Some studies examined several risk factors at the same time and all the studies investigated individual risk factors. Conclusions: A large number of suicides are committed in association with behavioral symptoms and many have intersectionality. Recognizing these factors may contribute to suicide prevention and mediation. Adolescent-friendly services provided in accordance with the distinct culture of each society are considered an effective measure for suicide prevention.